2012
DOI: 10.1099/jmm.0.044495-0
|View full text |Cite
|
Sign up to set email alerts
|

Ellagitannin from Quercus infectoria eradicates intestinal colonization and prevents renal injuries in mice infected with Escherichia coli O157 : H7

Abstract: The use of antimicrobial agents in the management of patients infected with Shiga toxinproducing Escherichia coli (STEC) O157 : H7 remains controversial. Here, we examined the antibacterial efficacy of a natural product, ellagitannin from Quercus infectoria (Qi 4), against the organism in a murine model. Streptomycin-pretreated mice were orogastrically inoculated with 2¾10 9 c.f.u. streptomycin-resistant E. coli O157 : H7. The results demonstrated a stable high level of STEC present in the faeces of the infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Treatment with 2× MIC did not reveal significant results, while with 4× MIC, the ETs were proved to be effective and the faeces showed to contain less STEC. The untreated groups showed endothelial cell injury, while the ET-treated groups showed no cell injury (Voravuthikunchai and Suwalak, 2012).…”
Section: In Vivo Studiesmentioning
confidence: 98%
“…Treatment with 2× MIC did not reveal significant results, while with 4× MIC, the ETs were proved to be effective and the faeces showed to contain less STEC. The untreated groups showed endothelial cell injury, while the ET-treated groups showed no cell injury (Voravuthikunchai and Suwalak, 2012).…”
Section: In Vivo Studiesmentioning
confidence: 98%
“…However, the emergence of new pathogens and the increase of multiantibiotic‐resistant pathogens necessitate the development of ever new antimicrobials . In recent years, by in vitro test, various extracts of HMs worldwide have shown promising inhibitory effects on intestinal epithelial cell adherence, intracellular invasion, and enteric colonization of certain potential or opportunistic pathogens, typically E. coli , Helicobacter pylori , Campylobacter jejuni , Enterococcus faecalis , Salmonella typhimurium , Bacillus subtilis , Klebsiella pneumoniae , Shigella dysenteriae , Pseudomonas aeruginosa . Inhibition of potential or opportunistic pathogens in vivo by HMs was also observed in relevant disease models.…”
Section: Hms and Gut Microbiotamentioning
confidence: 99%
“…Several studies have tested natural products for their ability to reduce or prevent Stx-induced cell or tissue damage in cell cultures in vitro or in animal infection models. An inhibition of cytotoxicity of Stx of E. coli O:157:H7 was found for white carob tree (Prosopsis alba) and Ziziphus mistol extracts (Pellarin et al, 2013) and for Ellagitannin from the Aleppo oak (Quercus infectoria) (Voravuthikunchai et al, 2012). Moreover, bacterial products such as lactic acid, linoleic acid, (Pittman et al, 2012), green tea extracts (Isogai et al, 1998(Isogai et al, , 2001, fruit juices (Nogueira et al, 2003), and other plant products (Takemasa et al, 2009;Lacombe et al, 2010;Lee and Stein, 2011;Sheng et al, 2016;Sewlikar and D'Souza, 2017;Patel et al, 2018) have been shown to have a beneficial effect on STEC-infected cells and animals alone or in combination of other agents, e.g., antibiotics.…”
Section: Natural Productsmentioning
confidence: 98%